Plang Edukasi Waktu Urai Sampah sebagai Media Informasi dan Pengingat Pengelolaan Sampah - Islamiah, Adinda Nurul; Pratiwi, Asti Dwi; Saifulloh, M.; Wiratama, Maulana Bagas Adi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
The educational signboard program on the decomposition time of inorganic waste in Titik Village, Semen District, Kediri Regency was implemented to raise public awareness of the impact of inorganic waste that is difficult to decompose. The Asset-Based Community Development (ABCD) approach was used to empower the community through five stages: discovery, dream, design, define, and destiny. The results of the activity showed an increase in residents' understanding of the types of inorganic waste and their decomposition times, such as plastic bottles (approximately 400 years), aluminum cans (80–200 years), milk cartons (5 years), and styrofoam (non-biodegradable). The signs installed at strategic locations serve as both an information medium and a reminder for the community to manage waste properly. This activity not only impacted changes in residents' behavior but also encouraged active participation and cooperation in maintaining environmental cleanliness.